Comparative mitogenomics elucidates the population genetic structure of Amblyomma testudinarium in Japan and a closely related Amblyomma species in Myanmar. (23rd June 2022) - Mohamed, Wessam Mohamed Ahmed; Moustafa, Mohamed Abdallah Mohamed; Thu, May June; Kakisaka, Keita; Chatanga, Elisha; Ogata, Shohei; Hayashi, Naoki; Taya, Yurie; Ohari, Yuma; Naguib, Doaa; Qiu, Yongjin; Matsuno, Keita; et al.
Abstract: Ticks are the second most important vector capable of transmitting diseases affecting the health of both humans and animals. Amblyomma testudinarium Koch 1844 (Acari: Ixodidae), is a hard tick species having a wide geographic distribution in Asia. In this study, we analyzed the composition of A. testudinarium whole mitogenomes from various geographical regions in Japan and investigated the population structure, demographic patterns, and phylogeographic relationship with other ixodid species. In addition, we characterized a potentially novel tick species closely related to A. testudinarium from Myanmar. Phylogeographic inference and evolutionary dynamics based on the 15 mitochondrial coding genes supported that A. testudinarium population in Japan is resolved into a star‐like haplogroup and suggested a distinct population structure of A. testudinarium from Amami island in Kyushu region. Correlation analysis using Mantel test statistics showed that no significant correlation was observed between the genetic and geographic distances calculated between the A. testudinarium population from different localities in Japan. Finally, demographic analyses, including mismatch analysis and Tajima's D test, suggested a possibility of recent population expansion occurred within Japanese haplogroup after a bottleneck event. Although A. testudinarium has been considered widespread and common in East and Southeast Asia, the current study suggested that potentially several cryptic Amblyomma spp. closely related to A. testudinarium are present in Asia.